The infield-outfield farming system as a major solution for sustainable management of the semi-natural and cultural heritage in Parque Natural da Serra da Estrela - Jansen, Jan (Lazaroa, 2009)
In this presentation a concise rationale is given to conserve landscape, semi-natural habitats and related cultural aspects in a large Natura 2000 area. It is explained why farmers and shepherds already functioned as managers of plant communities and EU directives avant-la-lettre. So far in Serra da Estrela restoration is needed for natural communities (mainly forests) only.As for semi-natural communities conservation is needed and continuation of the infield-outfield system is the provisional solution until new varieties of the traditional land-use system become available meeting modern criteria for socio-economic sustainability. The living cultural landscape of the Serra da Estrela might be used as a laboratory where many interrelationships on the species, community and landscape levels can be studied in situ, which can be useful as a reference to restoration projects in similar landscapes of by-gone days in Europe. Some examples are given of functional links between agriculture and nature. Until it is known in detail and including quantitative data of how these processes function, no reliable predictions on changes in biodiversity as a result of modern alternatives can be made.